2022
DOI: 10.1177/02673231221130926
|View full text |Cite
|
Sign up to set email alerts
|

The German media as amplifier of the political agenda: The economic policy framing of European conflicts in times of COVID-19

Abstract: Especially in times of (corona) crisis, the German press plays a crucial role in communicating Germany’s economic policy orientation, influencing how the crisis is communicated to the public. The issue of joint European debt has never been more visible than in these times, as has the threat of a new euro crisis—Italy in focus. This study explores the German media framing of coronavirus disease 2019 (COVID-19) using Italy as an example. Applying quantitative content analysis, the relative prevalence of frames r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the impact of media reporting on government approval varies depending on the ruling party, with social democrats facing harsher penalties than Christian democrats. Teschendorf (2022) studied how the German press framed economic policy during the COVID-19 pandemic, particularly focusing on the issue of joint European debt and the potential of a new euro crisis, using Italy as a case study. The study observed a paradigm shift in German media, moving from neoliberal to Keynesian views, reflecting Germany's policy shift towards European joint debt and greater fiscal integration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of media reporting on government approval varies depending on the ruling party, with social democrats facing harsher penalties than Christian democrats. Teschendorf (2022) studied how the German press framed economic policy during the COVID-19 pandemic, particularly focusing on the issue of joint European debt and the potential of a new euro crisis, using Italy as a case study. The study observed a paradigm shift in German media, moving from neoliberal to Keynesian views, reflecting Germany's policy shift towards European joint debt and greater fiscal integration.…”
Section: Discussionmentioning
confidence: 99%